Traditional organized crime in the modern world : Responses to socioeconomic change - van de Bunt, Henk; Siegel, Dina (Studies of Organized Crime, 2012)
Despite strenuous efforts from local, national, and international law enforcement, organized crime continues to thrive and prosper-even centuries-old crime outfits are surviving the global forces of mass migration and multinational business and finance. From traditional gangland enterprises such as narcotics, gambling, and prostitution, the world's mafias have moved into new sources of illegal income, including high-tech arms smuggling, money laundering, and identity fraud. Traditional Crime in the Modern World tracks these organizations-the Italian and Mexican mafias, Columbian drug cartels, Chinese triads, and others-across five continents as they adapt to change, and assesses their prospects in the short and long term. World events such as the collapse of the Soviet Union and the 9/11 terror attacks are discussed in the context of contributing to emerging markets for illicit goods and services, and to evolving partnerships among criminal entities. This timely volume: • Provides a comprehensive overview of how mafia-like structures function today. • Analyzes in depth national crime situations with global implications. • Examines the migration of organized crime groups and their operations in their new countries. • Gauges the influence of digital and other technologies on organized crime. • Where applicable, notes the links between organized crime and national political institutions. • Describes the impact of the global financial crisis on crime organizations. Concise, compelling, and deeply documented, Traditional Crime in the Modern World is an eye-opening resource for researchers in Criminology and Criminal Justice, particularly with an interest in organized crime and trafficking, as well as related topics of Demography, Political Science, and International Relations.